The Effect of Advertising, Exhibition and Event Marketing to Improve Awareness Awareness and its Impact on Intereststo Visit to Destination Religi Tour in Padang City (Case Study of Muslim Tourists from Malaysia) - Elfitra Desy Surya (International Conference of ASEAN Prespective and Policy (ICAP), 2018)
From the data released by the Tourism Office of West Sumatera Province, it is seen that tourist visit to West Sumatera tend to decrease from year to year .. However, this decline has made the industry players and the Tourism Office in West Sumatra both provinci and regency. The city began to think of how efforts should be made to increase the interest of visiting Muslim tourists from Malaysia. Because the achievement of Malaysian tourists visit per year to West Sumatra as many as 60,000 people in 2017, has not been achieved, although it has been pushed by running the event